Histological Findings of Organizing Pneumonia, Based on Transbronchial Lung Biopsy, May Predict Poor Outcome in Polymyositis and Dermatomyositis: Report of Two Autopsied Cases - Hiroshi OIWA; Takeshi KONDO; Masamoto FUNAKI; Toshiaki MORITO; Hiroshi YASUI; Toru KAMIYA (Archives of Rheumatology, 2018)
Interstitial lung disease in polymyositis and dermatomyositis is a serious complication, associated with poor prognosis. In this article, we describe two cases with histological findings of organizing pneumonia, based on transbronchial lung biopsy. One is a 66-year-old female patient with clinically amyopathic dermatomyositis with anti-melanoma differentiation-associated gene 5 antibody, and another is a 61-year-old female patient with polymyositis with anti-Jo-1 antibody. Both of our cases rapidly deteriorated to death, and autopsy findings showed diffuse alveolar damage. Our experience indicates that transbronchial biopsy findings of organizing pneumonia may be a poor prognostic factor in clinically amyopathic dermatomyositis and polymyositis, in spite of the profile of myositis-specific antibodies.